Adjective Learning in Young Typically Developing Children and Children With Developmental Language Disorder: A Retrieval-Based Approach - Leonard, Laurence B. (J Speech Lang Hear Res, 2019)
PURPOSE: There are strong retention benefits when learners frequently test themselves during the learning period. This practice of repeated retrieval has recently been applied successfully to children's word learning. In this study, we apply a repeated retrieval procedure to the learning of novel adjectives by preschool-age children with developmental language disorder (DLD) and their typically developing (TD) peers. We ask whether the benefits of retrieval extend to children's ability to apply the novel adjectives to newly introduced objects sharing the same characteristics as the objects used during the learning period. METHOD: Fourteen children with DLD (M (age) = 62.64 months) and 13 TD children (M = 62.54 months) learned novel adjectives in 2 sessions. For each child, half of the adjectives were learned in a repeated spaced retrieval condition, and half were learned in a repeated study–only condition. Recall was assessed immediately after the second learning session and 1 week later. A recognition test was also administered at the 1-week mark. RESULTS: On the recall tests, for both groups of children, recall was better for adjectives learned in the repeated spaced retrieval condition. Adjectives learned by the 2nd day were retained 1 week later. Every adjective correctly applied to an object used during the learning period was also extended accurately to new objects with the same characteristics. On these recall tests, the children with DLD did not differ from the TD group in the number of items recalled, though their phonetic accuracy was lower. On the recognition test, the DLD group showed greater accuracy for adjectives that had been learned in the repeated spaced retrieval condition than for those learned in the repeated study condition, whereas the TD group performed at high levels in both conditions. CONCLUSION: Repeated spaced retrieval appears to provide an effective boost to word learning. Because its benefits are seen even when a word must be extended to new objects, the application of this procedure seems well suited for learning new language material rather than being limited to item-specific memorization.